Isomerization of linear c5-c7 over pt loaded on protonated fibrous silica@y zeolite (Pt/Hsi@Y) - S., Triwahyono; A. A., Jalil; N. S., Jamari; M. L., Firmansyah; N. A., Fatah; S. M., Izan; S. F., Jamian; Herma Dina, Setiabudi (Universiti Malaysia Pahang, 2018)
Silica-based fibrous material has been extensively studied by researchers after the discovery of fibrous silica nanosphere (KCC-1) by Polshettiwar et al., 2010. The KCC-1 was first prepared using the microwave-assisted hydrothermal technique exhibited excellent properties, including a high surface area, a fibrous surface morphology, good thermal and hydrothermal stabilities and mechanical stability. Moon, et al., (2012) reported that the mesoporous silica with fibrous morphology has high surface area compared with a typical hexagonal or cubic pore structure which suitable for good catalytic support. Previous study has many discovered related to the acid-catalyzed for isomerization reaction. They discovered that the isomerization supports must have appropriated acidity for the good catalytic activity. However, the KCC-1 which fully composed with silica does not provided an adequate acid sites to promote acid-catalyzed isomerization reaction [1,2]. In the present work, newly combined zeolite-based with fibrous silica was prepared via self-assembly process in the microemulsion system. This new catalyst has a potential to overcome inadequate acidity provided by KCC-1. Therefore, implementation of combined silica based material with zeolite enhanced the acidity of the catalyst to overcome the inadequate acidity provided by solely silica of KCC-1. The high acidity will enhanced the isomerization reaction towards producing high octane number gasoline [3].